The Critical Role of Small RNAs in Regulating Plant Innate Immunity - Saquib Waheed; Muhammad Anwar; Muhammad Asif Saleem; Jinsong Wu; Muhammad Tayyab; Zhangli Hu (Biomolecules, 2021)
Plants, due to their sessile nature, have an innate immune system that helps them to defend against different pathogen infections. The defense response of plants is composed of a highly regulated and complex molecular network, involving the extensive reprogramming of gene expression during the presence of pathogenic molecular signatures. Plants attain proper defense against pathogens through the transcriptional regulation of genes encoding defense regulatory proteins and hormone signaling pathways. Small RNAs are emerging as versatile regulators of plant development and act in different tiers of plant immunity, including pathogen-triggered immunity (PTI) and effector-triggered immunity (ETI). The versatile regulatory functions of small RNAs in plant growth and development and response to biotic and abiotic stresses have been widely studied in recent years. However, available information regarding the contribution of small RNAs in plant immunity against pathogens is more limited. This review article will focus on the role of small RNAs in innate immunity in plants.